The Magic school bus membuat pelangi. buku tentang warna Joanna Cole ; ilustrasi Bruce Degen ; alih bahasa Andri Kurniawan - COLE, Joanna; Degen, Bruce; Kurniawan, Andri (Elex Media Komputindo, 2002)
[32] hlm ilus 21 cm